Unusual Sites for Hemodialysis Vascular Access Construction and Catheter Placement: A Review. Issue 6 (June 2015) - Lew, Susie Q.; Nguyen, Bao-Ngoc; Ing, Todd S.
As more end-stage renal disease patients require hemodialysis and live longer, many will fail to develop or maintain a functioning upper extremity vascular access. When a patient exhausts vascular access sites in the upper extremities, new fistulas and grafts can be constructed in the lower extremities, thorax, and abdomen as long as a pair of proximate artery and vein provide adequate blood inflow and outflow, respectively. When only a moderate size vein with adequate blood flow provides a conduit to either a patent superior or inferior vena cava, inserting a double-lumen venous hemodialysis catheter can provide temporary or permanent access. We review the literature and report the unusual sites for hemodialysis vascular access and catheter placement.